Dataset for estimating the photosynthetic oxygen production of Laminaria hyperborea off the island of Helgoland in summer 2014 - Kiara Franke; Lisa C Matthes; Angelika Graiff; Ulf Karsten; Inka Bartsch (PANGAEA, 2023)
The impact of variable underwater photosynthetically active radiation (PAR) and photosynthetic parameters on photosynthetic oxygen production of Laminaria hyperborea off the island of Helgoland (North Sea, Germany) was investigated throughout summer 2014. L. hyperborea was sampled along a depth gradient (0.5, 2, 4, 6 m) and discs from three different blade regions (5, 25 and 50 cm above the stipe-blade transition zone) were set into photosynthesis versus irradiance (PI) curves. After cutting and before the oxygen incubation, maximum quantum yield (Fv/Fm) were measured as a health indicator. PI-curve parameters were normalized to either fresh mass or disc area. Additionally, chlorophyll a content was measured in each disc and normalized to the same two parameters as PI parameters. In situ PAR was measured in different depths (1.2, 2.9, 4.4, 6.6 m) to gain daily diffuse vertical attenuation coefficient (Kd). PAR along the vertical depth profile was calculated and together with PI-curve parameters oxygen production was calculated along the vertical depth profile. Leaf area index (Pehlke and Bartsch, 2008) was used to extrapolate oxygen production rates to seafloor and a photosynthetic quotient (PQ) of 1.18 (Miller III et al., 2009) to convert rates into carbon fixation rates. This net primary production (NPP) was given along the vertical depth profile based on different Kd values (daily Kd, mean Kd, minimum Kd, maximum Kd).